Three new species of the oonopid spider genus Ischnothyreus (Araneae: Oonopidae) from Tioman Island (Malaysia) - Kranz-Baltensperger, Yvonne (Zootaxa, 2012)
Three new species of the genus Ischnothyreus (I. tioman, I. tekek and I. namo) are described from Tioman Island off theeastern coast of Peninsular Malaysia. Two of the described species show peculiar cheliceral modifications that are discussed with respect to similar structures found in other families.